Natural Biostimulants Elicit Plant Immune System in an Integrated Management Strategy of the Postharvest Green Mold of Orange Fruits Incited by Penicillium digitatum - La Spada, Federico; Aloi, Francesco; Coniglione, Maurizio; Pane, Antonella; Cacciola, Santa Olga (Frontiers in Plant Science, 2021)
This study was aimed at testing the integrated use of a natural biostimulant based on seaweed (Ascophyllum nodosum) and plant (alfalfa and sugarcane) extracts and reduced dosages of the conventional synthetic fungicide Imazalil (IMZ) to manage postharvest rots of orange fruits. The following aspects were investigated: i. the effectiveness of postharvest treatment with natural biostimulant alone or in mixture with IMZ at a reduced dose against green mold caused by Penicillium digitatum; ii. the differential expression of defense genes in orange fruits treated with the natural biostimulant both alone and in combination with a reduced dose of IMZ; iii. the persistence of the inhibitory activity of both biostimulant and the mixture biostimulant/IMZ against green mold; iv. the residue level of fungicide in citrus peel when applied alone or in combination with the biostimulant. Treatments with the chemical plant resistance-inducer potassium phosphite, alone or with a reduced dose of IMZ, were included for comparison. The mixture natural biostimulant and IMZ at a low dose reduced consistently the incidence and severity of fruit green mold and induced a significant increase of the expression level of β-1,3-glucanase-, peroxidase-, and PAL-encoding genes in fruit peel, suggesting that the natural biostimulant elicits a long-lasting resistance of citrus fruits to infections by P. digitatum. Interestingly, the residual concentration of IMZ in fruits treated with the mixture biostimulant/fungicide was significantly lower than in fruits treated only with the fungicide at the same dose and by far below the threshold values set by the European Union. This study made it possible to i. conceive a practical and more eco-friendly alternative to the conventional postharvest management of green mold of citrus fruits, based almost exclusively on the use of synthetic fungicide IMZ, alone or mixed with potassium phosphite, and ii. provide a better insight into the mechanisms of disease resistance induction by biostimulants.